Treatment with bergamot (Citrus bergamia) leaves extract attenuates leptin resistance in obese rats. (1st May 2023) - Nakandakare-Maia, Erika Tiemi; Siqueira, Juliana Silva; Ferron, Artur Junio Togneri; Vieira, Taynara Aparecida; Palacio, Thiago Luiz Novaga; Grandini, Núbia Alves; Garcia, Jéssica Leite; Belin, Matheus Antonio; Altomare, Alessandra; Baron, Giovanna; Aldini, Giancarlo; Francisqueti-Ferron, Fabiane Valentini; et al.
Abstract: Low-grade chronic inflammation in obesity is associated with leptin resistance. In order to alleviate this pathological condition, bioactive compounds capable of attenuating oxidative stress and inflammation have been researched, and bergamot ( Citrus bergamia ) presents these properties. The aim was to evaluate the effect of bergamot leaves extract on leptin resistance in obese rats. Animals were divided into 2 groups: control diet (C, n = 10) and high sugar-fat diet (HSF, n = 20) for 20 weeks. After detecting hyperleptinemia, animals were divided to begin the treatment with bergamot leaves extract (BLE) for 10 weeks: C + placebo (n = 7), HSF + placebo (n = 7), and HSF + BLE (n = 7) by gavage (50 mg/kg). Evaluations included nutritional, hormonal and metabolic parameters; adipose tissue dysfunction; inflammatory, oxidative markers and hypothalamic leptin pathway. HSF group presented obesity, metabolic syndrome, adipose tissue dysfunction, hyperleptinemia and leptin resistance compared to control group. However, the treated group showed a decrease in caloric consumption and attenuation of insulin resistance. Moreover, dyslipidemia, adipose tissue function, and leptin levels showed an improvement. At the level of the hypothalamus, the treated group showed a reduction of oxidative stress, inflammation and modulation of leptin signaling. In conclusion, BLE properties were able to improve leptin resistance through recovery of the hypothalamic pathway. Graphical abstract: Image 1 Highlights: Chronic inflammation present in obesity is associated with leptin resistance. Bergamot attenuated inflammation and oxidative stress in the hypothalamus. Bergamot leaves extract attenuated metabolic syndrome. Bergamot leaves extract treatment recovered leptin pathway in the hypothalamus.